Detection and Imaging of the Plant Pathogen Response by Near‐Infrared Fluorescent Polyphenol Sensors - Nißler, Robert; Müller, Andrea T.; Dohrman, Frederike; Kurth, Larissa; Li, Han; Cosio, Eric G.; Flavel, Benjamin S.; Giraldo, Juan Pablo; Mithöfer, Axel; Kruss, Sebastian (Angewandte Chemie International Edition, 2022)
Plants use secondary metabolites such as polyphenols for chemical defense against pathogens and herbivores. Despite their importance in plant pathogen interactions and tolerance to diseases, it remains challenging to detect polyphenols in complex plant tissues. Here, we create molecular sensors for plant polyphenol imaging that are based on near‐infrared (NIR) fluorescent single‐wall carbon nanotubes (SWCNTs). We identified polyethylene glycol–phospholipids that render (6,5)‐SWCNTs sensitive (Kd=90 nM) to plant polyphenols (tannins, flavonoids, …), which red‐shift (up to 20 nm) and quench their emission (ca. 1000 nm). These sensors report changes in total polyphenol level after herbivore or pathogen challenge in crop plant systems (Soybean Glycine max) and leaf tissue extracts (Tococa spp.). We furthermore demonstrate remote chemical imaging of pathogen‐induced polyphenol release from roots of soybean seedlings over the time course of 24 h. This approach allows in situ visualization and understanding of the chemical plant defense in real time and paves the way for plant phenotyping for optimized polyphenol secretion. Molecular sensors for plant polyphenol imaging based on near‐infrared (NIR) fluorescent single‐wall carbon nanotubes (SWCNTs) are presented. These sensors probe the polyphenol content in complex biological systems such as the plant rhizosphere. In summary, this approach enables real‐time spatiotemporal visualization of plant defense via polyphenols release.